Devil may cry [videorecording (DVD)] : the animated series : the complete collection - Itagaki, Shin, 1974-; Inoue, Toshiki (FUNimation Entertainment, 2008)
"Cursed to live as both monster and man, Dante must spend his life fighting the demonic forces of darkness. Brandishing his sword, Rebellion, and his always-loaded guns, Ebony and Ivory, Dante is more than happy to send the demons back to Hell. Especially when there's money to be made. The wildly popular video game is now a series, and this time, there's no sympathy for the Devil"--Container.